Chemometric optimisation of pressurised liquid extraction for the determination of alliin and S‐allyl‐cysteine in giant garlic (Allium ampeloprasum L.) by liquid chromatography tandem mass spectrometry. Issue 6 (28th March 2021) - Peterssen‐Fonseca, Darlene; Henríquez‐Aedo, Karem; Carrasco‐Sandoval, Jonathan; Cañumir‐Veas, Juan; Herrero, Miguel; Aranda, Mario
Abstract: Introduction: Giant garlic is a functional food that contains different kinds of bioactive molecules with beneficial effects on chronic noncommunicable diseases like diabetes and cardiovascular conditions. Considering biosynthesis pathways, abundance, and biological activity, alliin and S‐allyl‐cysteine were used as chemical markers of organosulphur compounds present in giant garlic. Objective: To establish a chemometric optimisation of pressurised liquid extraction for the determination of alliin and S‐allyl‐cysteine in giant garlic by liquid chromatography tandem mass spectrometry (LC–MS/MS). Methodology: Samples were blanched (ca. 90°C for 10 min) to inactivate alliinase and γ‐glutamyl transpeptidase enzymes and then freeze‐dried. Chemometric optimisation was performed via response surface methodology based on central composite design (CCD). Organosulphur compound yields were determined applying a validated LC–MS/MS method in multiple reaction monitoring (MRM) mode using the following transitions: for alliin m/z 178 → 74 and for S‐allyl‐cysteine m/z 162 → 41. Results: According to CCD results, under constant conditions of pressure (1500 psi) and time (20 min), the optimal conditions for pressurised liquid extraction of alliin and S‐allyl‐cysteine were 70.75 and 68.97% v/v of ethanol in extraction solvent and 76.45 and 98.88°C as extraction temperature, respectively. Multiple response optimisation for the simultaneous extraction of both organosulphur compounds was established via desirability function. Under these conditions, 2.70 ± 0.27 mg g −1 dry weight (DW) of alliin and 2.79 ± 0.22 mg g −1 DW of S‐allyl‐cysteine were extracted. Conclusions: These results clearly demonstrated that pressurised liquid extraction is an efficient green technique to extract bioactive organosulphur compounds from giant garlic. Extraction yields were significantly ( p  < 0.05) higher than those obtained with conventional ultra‐turrax extraction. Abstract : Giant garlic is a functional food with beneficial effects on chronic noncommunicable diseases. This work reports the optimisation of pressurised liquid extraction of S‐allyl‐cysteine and alliin from giant garlic. Employing a central composite design, optimal conditions for alliin and S‐allyl‐cysteine extraction were, respectively, 70.75 and 68.97% v/v of ethanol and 76.45 and 98.88°C. Under these conditions, 2.70 ± 0.27 mg g −1 dry weight (DW) of alliin and 2.79 ± 0.22 mg g −1 DW of S‐allyl‐cysteine were extracted, values significantly higher than those obtained with conventional extraction.